2021
DOI: 10.1155/2021/1522250
|View full text |Cite|
|
Sign up to set email alerts
|

Correlation between LRP1B Mutations and Tumor Mutation Burden in Gastric Cancer

Abstract: Background. It has been shown that low-density lipoprotein receptor-related protein 1B (LRP1B) mutations correlate with tumor mutation burden (TMB) and prognosis in patients with melanoma and non-small-cell lung cancer, while the relationship between LRP1B mutations and TMB in gastric cancer needs further study. This study is aimed at exploring the relationship between LRP1B mutations and TMB in gastric cancer. Methods. Mutation frequency profiles of the genes in patients with gastric cancer in TCGA-STAD datas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 35 publications
3
10
0
Order By: Relevance
“…7E. As expect, most genes were participating in various tumor-associated biological processes in STAD like TP53, TTN and www.nature.com/scientificreports/ LRP1B [54][55][56] . Then, the differentially mutated frequencies were analyzed between the high-risk group and low-risk group, and 928 differentially mutated genes were obtained by Fisher's exact test (p < 0.05).…”
Section: The Different Somatic Mutations Patterns Between High-risk G...supporting
confidence: 56%
“…7E. As expect, most genes were participating in various tumor-associated biological processes in STAD like TP53, TTN and www.nature.com/scientificreports/ LRP1B [54][55][56] . Then, the differentially mutated frequencies were analyzed between the high-risk group and low-risk group, and 928 differentially mutated genes were obtained by Fisher's exact test (p < 0.05).…”
Section: The Different Somatic Mutations Patterns Between High-risk G...supporting
confidence: 56%
“…Tumor mutation burden (TMB), de ned as the total number of mutations (non-synonymous mutations) detected per million bases in the tumor genome, is a potential biomarker of cancer invasion and metastasis 47 . Our study demonstrated that the high-risk group showed a lower gene mutation density than the low-risk group.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with LRP1B mutation were identified to be associated with prolonged survival in both melanoma and NCLC cohorts [ 8 ]. Moreover, LRP1B is thought to be a marker of TMB to guide immunotherapy [ 13 , 14 , 26 ]. However, these studies have only conducted multi-omics studies without exploring the specific mechanism.…”
Section: Discussionmentioning
confidence: 99%